The influence of particle size towards the resistivity and chargeability value for groundwater investigation interpretation - Abd Malik, Ahmad Khairul (2021)
Electrical resistivity tomography is a non-destructive method of groundwater surveying where the current is being injected into the ground and the value of the subsurface resistivity and chargeability were determined. One of the major problems in groundwater surveying is the interpretation of the groundwater aquifer under saturated condition. The overlapping resistivity and chargeability value under a saturated condition is a major concern in groundwater aquifer interpretation. In this study, the effects of particle size and the interrelationship between the different particle sizes were assessed towards the resistivity and chargeability value. There were 17 samples used in this study ranges from gravel, sand, silt and clay sizes. The materials used to conduct the testing were granitic rock and river sand. Quartz and kaolinite dominated samples were used for the silt and clay sample. The device used for the experiment is Terrameter LS 2 to conduct the resistivity and induced polarization tests. The electrical testing follow the ASTM G57 and ASTM G187/AASHTO T-288 standards for the soil box with volume of 270 cm and soil cylinder with volume of 2714 cm 3 respectively. The resistivity value for the gravel ranges from 177 Ωm at its highest to 128 Ωm at its lowest. The resistivity value for the sand ranges from 121 Ωm at its highest to 86 Ωm at its lowest. The resistivity value of the two silt and clay samples were 37 Ωm and 56 Ωm at the point of liquid limit. The chargeability value for the gravel ranges from 5.6 ms to 7.9 ms with decreasing particle size. The highest chargeability value for sand is 12.3 ms and the lowest is 2.0 ms. The silt and clay samples chargeability were 1.7 ms and 1.2 ms, respectively. The resistivity and chargeability for water used in this study were 101.7 Ωm and 0.41 ms. This study helps in clarifying the effect of particle size for resistivity and chargeability value as the larger particle size increases the resistivity value and decreases the chargeability value of water due to porosity and improve the understanding of the electrical resistivity tomography for groundwater investigation interpretation.